Evaluation of Decayed, Missing and Filled Teeth (DMFT) index in the 12 Years Old Students of Tehran City, Iran - Azam Goodarzi; Alireza Heidarnia; Sedigheh Sadat Tavafian; Mohammad Eslami (Universidade Estadual de Campinas, 2018)
Aim: The main aim of this study was to Evaluate of Decayed, Missing and Filled Teeth (DMFT) Index in 12 Year Old Students of Tehran City, and to identify related factors that affect dental caries within this group. Methods: A cross-sectional survey was conducted among students of 12 years old in Tehran, Iran. Dental caries status was assessed in terms of decayed teeth (DT), filled teeth (FT) and decayed, missing and filled teeth (DMFT). "Data were analysed using SPSS version 22; a multivariate regression analysis was used to determine statistically significant associations between DMFT and other variables (p < 0.05). Results: A total of 416 respondents participated in the study. The mean age of the students was10.94 (SD=0.628) years, and the mean DMFT was 1.03 (SD=1.41). So that, in this study DT (0.53 ± 0.95) had the highest and MT (0.14 ± 0.47) had the lowest mean. A multivariate regression analysis model results showed a significant relation between high DMFT scores and such variables as increasing age, lower levels of mother's education, higher family income, lower frequency of tooth brushing and dental flossing, having a history of no visits to the dentist (P<0.05). Conclusion: The current study shows that Iranian female students have a poor oral health behavior, as very few subjects use dental floss on a regular basis. Although there appeared to be a significant relationship between caries scores and demographic factors such as age and socio-behavioral variables include  family income, the level of mothers' education, the frequency of dental brushing and flossing, and both the frequency and type of visit to a dentist.